2009
DOI: 10.1080/10934520902719886
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of arsenicosis in a rural village of Cambodia

Abstract: Ninety-seven subjects belonging to 40 families in a village in Cambodia were examined in a health camp where all the cases with skin disease assembled. These people had evidences of chronic arsenic exposure from reports of testing of water samples and of hair and/or nail studied. Seventy cases were diagnosed to be suffering from arsenicosis (Clinically and laboratory confirmed according to WHO criteria) as all these cases had evidences of pigmentation and/or keratosis characteristic of arsenicosis and history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Some skindiseased children have reported severe itching on exposure to sunlight; this effect was reported for the first time in West Bengal India [1]. These findings were also consistent with the study conducted in Cambodia [51] where few cases were diagnosed to be suffering from arsenicosis, as all had evidence of pigmentation and/or keratosis characteristic of arsenicosis. On the other hand, our survey demonstrated that the people of studied towns have poor socioeconomic status.…”
Section: Discussionsupporting
confidence: 78%
“…Some skindiseased children have reported severe itching on exposure to sunlight; this effect was reported for the first time in West Bengal India [1]. These findings were also consistent with the study conducted in Cambodia [51] where few cases were diagnosed to be suffering from arsenicosis, as all had evidence of pigmentation and/or keratosis characteristic of arsenicosis. On the other hand, our survey demonstrated that the people of studied towns have poor socioeconomic status.…”
Section: Discussionsupporting
confidence: 78%
“…Major affected regions of South-East Asia region the basin of the Ganga-Brahmaputra-Meghna Rivers and the Mekong Delta. [1,2] Although since reported across different states in Eastern India, the occurrence of disease resulting from arsenic toxicity was reported in West Bengal as early as 1983. [3] Besides pigmentation and keratosis, arsenicosis produces systemic manifestations including chronic respiratory disease, peripheral neuropathy, liver fibrosis, edema of legs, anemia and cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Human exposure has been demonstrated through studies of various biomarkers (Kubota et al 2006;Gault et al 2008) and cases of arsenic poisoning (arsenicosis) have been recorded by Mazumder et al (2009), amongst others. It is estimated that over 100,000 people are exposed in Cambodia, with the majority of those people living in Kandal province .…”
Section: Labour Markets and Shadow Wage Ratesmentioning
confidence: 99%